The (Other) Deleveraging - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2012)
Deleveraging has two components--shrinking of balance sheets due to increased haircuts/shedding of assets, and the reduction in the interconnectedness of the financial system. We focus on the second aspect and show that post-Lehman there has been a significant decline in the interconnectedness in the pledged collateral market between banks and nonbanks. We find that both the collateral and its associated velocity are not rebounding as of end-2011 and still about USD 4-5 trillion lower than the peak of USD 10 trillion as of end-2007. This paper updates Singh (2011) and we use this data to compare with the monetary aggregates (largely due to QE efforts in US, Euro area and UK), and discuss the overall financial lubrication that likely impacts the conduct of global monetary policy.